O discurso da revista Nova Escola em contextos educativos: prescrições acerca das tecnologias digitais - Pergher, Crislaine Eduarda (2020)
This dissertation presents a discursive textual analysis of the reports that the Nova Escola Magazine publishes about the presence of digital technologies in education. This is a bibliographic and documentary research, comprising six years of publication of the Magazine, from 2013 to 2018, with 23 samples studied, out of a total of 30 reports selected to compose the corpus of analysis. The period defined for this research is justified by expressing changes in information and communication technologies, with a strong incidence of digital processes in the lives of young people who now attend schools. The choice of Nova Escola Magazine as a research field is due to the fact that it is an object of significant circulation in Brazilian schools of basic education and widely used by teachers in their pedagogical dynamics. The general objective of the dissertation is to understand the pedagogical discourse published in the Nova Escola Magazine about the presence and use of digital technologies in school contexts. Within the scope of specific objectives, it is intended: a) to understand the historical context of Nova Escola Magazine, its structuring and organization, as well as to analyze its production conditions in market contexts; b) contextualize the presence of the media in education and identify how technological advances impact on schools and individuals who circulate in it; c) understand the method of discursive textual analysis and operate with its procedures in relation to Nova Escola Magazine. The results indicate that Nova Escola Magazine expresses a prescriptive pedagogical discourse regarding the use of digital technologies in schools in that it presents a very timid conduct with regard to critically discussing pedagogical practice, to deepen reflection on social and cultural diversity, present in schools and to offer a more consistent analysis of learning. It was also noted the limited character of its effort to problematize the significant inequality of access to technological resources in the different educational contexts. It is concluded that the Lemann Foundation, sponsor of the Nova Escola, operates a place of power by disseminating a given pedagogical culture and a certain conception of market education and based on technical-instrumental rationality.